Effect of Structured Education and Antihypertensive MedicationsAdherence to Decrease Blood Pressure for Hypertension inElderly: a Randomized Controlled Trial - Khomaini, Ayatullah; Setiati, Siti; Lydia, Aida; Dewiasty, Esthika (UI Scholars Hub, 2017)
Introduction. Hypertension is one of the important problems in elderly due to high impact of cardiovascular complications. Education and antihypertensive medication adherence are considered as influence factors in a holistic and comprehensive hypertension treatment. This study was conducted to determine the effect of structured education and antihypertensive medication adherence in decreasing blood pressure as part of the hypertension treatment in elderly patients. Methods. A randomized clinical trial was conducted in October 2012 to February 2013 on hypertensive elderly patients at Cipto Mangunkusumo hospital, Jakarta. Subjects were divided into 3 groups: group I was received structured education and checklist, group II was received structured education, and group III was received checklist without structured education. Structured education was given 3 times per month for 90 days. Systolic and diastolic blood pressure (SBP and DBP) were measured on day-1 and day-90, then analyzed with anova test. Results. A total of 182 subjects that consisted of 60 subjects in group I, 61 subjects in group II and 61 subjects in group III was included in this study. Analysis results showed a decrease of SBP in group I, II and III to 130 (range 90-179) mmHg, 135 (range 80-174) mmHg and 133 (range 102-209) mmHg, respectively (p=0.04). Diastolic blood pressure (DBP) in group I, II, and III decreased to 70 (range 48-100) mmHg, 74 (range 45-103) mmHg and 78 (range 60-102) mmHg, respectively (p <0.001). Conclusions. Structured education significantly decreased systolic and diastolic blood pressure in elderly hypertensive patients, while adherence to antihypertensive medication did not affect signicifantly.